2015
DOI: 10.1111/ics.12208
|View full text |Cite
|
Sign up to set email alerts
|

Oxidization of squalene, a human skin lipid: a new and reliable marker of environmental pollution studies

Abstract: Synopsis A review of the oxidization of squalene, a specific human compound produced by the sebaceous gland, is proposed. Such chemical transformation induces important consequences at various levels. Squalene by‐products, mostly under peroxidized forms, lead to comedogenesis, contribute to the development of inflammatory acne and possibly modify the skin relief (wrinkling). Experimental conditions of oxidation and/or photo‐oxidation mechanisms are exposed, suggesting that they could possibly be bio‐markers of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
84
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(88 citation statements)
references
References 44 publications
3
84
0
1
Order By: Relevance
“…Among the ingredients of SSL, squalene, a key biosynthetic precursor of cholesterol secreted by SGs, and α-tocopherol (vitamin E) secreted together with lipids from sebaceous gland, provide collaboratively antioxidant protection to the skin surface [135][136][137]. In addition, the by-products, squalene peroxides, produce during squalene oxidation, are considered to be involved in inflammatory and immunologically determined skin diseases, such as acne, atopic and seborrheic dermatitis as well as in skin cancerogenesis [138]. A recent study in China showed that the urban polulation has a lower squalene/lipid ratio than the rural one, which may mean that reduction of squalene is induced by environmental pollutants [137].…”
Section: Sebaceous Glands and Skin Skin Detoxificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the ingredients of SSL, squalene, a key biosynthetic precursor of cholesterol secreted by SGs, and α-tocopherol (vitamin E) secreted together with lipids from sebaceous gland, provide collaboratively antioxidant protection to the skin surface [135][136][137]. In addition, the by-products, squalene peroxides, produce during squalene oxidation, are considered to be involved in inflammatory and immunologically determined skin diseases, such as acne, atopic and seborrheic dermatitis as well as in skin cancerogenesis [138]. A recent study in China showed that the urban polulation has a lower squalene/lipid ratio than the rural one, which may mean that reduction of squalene is induced by environmental pollutants [137].…”
Section: Sebaceous Glands and Skin Skin Detoxificationmentioning
confidence: 99%
“…A recent study in China showed that the urban polulation has a lower squalene/lipid ratio than the rural one, which may mean that reduction of squalene is induced by environmental pollutants [137]. Moreover, squalene peroxides are proposed as a reliable marker of environmental pollutants in the skin [138].…”
Section: Sebaceous Glands and Skin Skin Detoxificationmentioning
confidence: 99%
“…In acne, qualitative and quantitative sebum modifications throughout increased sebum secretion increased squalene/oxidized squalene and increased free fatty acids have been observed 13. In addition, squalene oxidization has been identified as a marker of environmental pollution 14. The quantitative lipid analysis confirmed that the test care applied adjunctively for 90 days to a fixed combination and a standard emollient significantly ( P < 0.05) improved and equilibrated the quantitative composition of the sebum in patients with mild acne.…”
Section: Discussionmentioning
confidence: 69%
“…The availability of reliable and specific markers of airborne pollution upon skin would allow to evaluate and quantify the cutaneous impact of this phenomenon, as well as to assess the effectiveness of ingredients or finished products in counteracting detrimental effects of air pollutants. Recently, the oxidation of squalene has been recognized as a useful model [31]. Squalene, a high-unsaturated triterpene produced by human sebaceous glands and present in sebum with an average concentration of 12%, is very prone to oxidation and is one of the main targets of oxidative stress induced by air pollution.…”
Section: Introductionmentioning
confidence: 99%